2023
DOI: 10.3390/biomedicines11051402
|View full text |Cite
|
Sign up to set email alerts
|

Viral Coinfection of Children Hospitalized with Severe Acute Respiratory Infections during COVID-19 Pandemic

Abstract: The main pathogens of severe respiratory infection in children are respiratory viruses, and the current molecular technology allows for a rapid and simultaneous detection of a wide spectrum of these viral pathogens, facilitating the diagnosis and evaluation of viral coinfection. Methods: This study was conducted between March 2020 and December 2021. All children admitted to the ICU with a diagnosis of SARI and who were tested by polymerase chain reaction on nasopharyngeal swabs for SARS-CoV-2 and other common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Similarly, a systematic review conducted by Li et al [45] concluded that overall viral co-detection did not result in significant differences in disease course compared to RSV alone; however, RSV-HMPV co-detection trended towards a longer length of hospitalisation. Previous studies examining RSV co-detection have not shown a consistent association between coinfection and severity [44][45][46][47][48].…”
Section: Coinfection Of Respiratory Syncytial Virus Covid-19 and Othe...mentioning
confidence: 81%
“…Similarly, a systematic review conducted by Li et al [45] concluded that overall viral co-detection did not result in significant differences in disease course compared to RSV alone; however, RSV-HMPV co-detection trended towards a longer length of hospitalisation. Previous studies examining RSV co-detection have not shown a consistent association between coinfection and severity [44][45][46][47][48].…”
Section: Coinfection Of Respiratory Syncytial Virus Covid-19 and Othe...mentioning
confidence: 81%
“…A recent analysis of children with severe respiratory infections is an example (Figure 1). 7 Many COVID-positive patients were also positive for a second virus (58/137 = 42%); indeed, co-infections were more frequent than among COVID-negative patients (102/469 = 22%). These data suggest viral infections can occur in clusters, contrary to the claim by Locke and Aberegg.…”
mentioning
confidence: 96%
“…We believe, therefore, the conflicting debates around Occam's razor have endured for centuries and will not end soon. 7 Findings suggest a substantial frequency of co-infections, particularly in patients with COVID virus infection. Interpretation suggests a positive rather than inverse association between viral infections.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding pediatric cases, researchers have also investigated the prevalence of respiratory viruses and their coinfections in children with severe respiratory infections (SARIs) [28]. The five most frequent coinfections identified were human rhinovirus (hRV)/SARS-CoV-2 (17.91%), hRV/respiratory syncytial virus (RSV) (14.18%), RSV/SARS-CoV-2 (12.69%), hRV/human bocavirus (BoV) (10.45%), and hRV/adenovirus (AdV) (8.21%) [29]. These findings offer valuable insights into the complexity of pediatric respiratory infections and the need for tailored interventions.…”
mentioning
confidence: 99%